Animal behavior missing from data archives. (November 2021) - Miller, Sara E.; Jernigan, Christopher M.; Legan, Andrew W.; Miller, Caitlin H.; Tumulty, James P.; Walton, Alexander; Sheehan, Michael J.
Abstract : An investigation into animal behavior data archiving practices revealed low rates of data archiving, frequent issues with archived data, and a near absence of multimedia data from data archives. Increasing archiving of animal behavior data will improve the integrity of current studies and enable new avenues of research.